Priorytety wartości podstawowych w świadomości maturzystów puławskich (1994–2009–2016) - Mariański, Janusz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
In this article we discuss the functioning of some basic values in the consciousness of Puławy high school graduates. We pay attention to both the understanding of basic values (content) and the recognized superiority of one value over another (preference). We assume that in the conditions of radical social changes there is a clear re-evaluation of values, loss of meaning of some values and an increase in importance of others. High school graduates were presented with a test of alternative sentences, containing several pairs of statements, asking them to choose those that are closer to their views (binary choices).These statements concerned values which, even if they do not oppose each other, but complement each other and realize through each other, may be subject to preferences. Answers to the research problem will be sought in empirical materials collected in the years 1994-2009-2016 among both high school and tech school graduates in Puławy. Sociological analyses show that more or less the same proportion of the surveyed high school graduates support an individualistic understanding of freedom (“everyone does what they want”), as well as an objective approach (freedom related to good and truth). In this respect, boys and teenagers from high schools, living in Puławy and those loosely connected with religion or non-believers hold rather an individualistic-liberal attitude. In the years 1994-2016, there were no significant changes in the consciousness of high school graduates regarding the understanding of freedom in its subjective and objective version.